PENGARUH KUALITAS KEHIDUPAN KERJA, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. Djarum Kudus) - Nurul, Cut Rizky; Rahardja, Edy (Diponegoro Journal of Management, 2019)
This study aims to determine and analyze the influence of quality of work life, work motivation, and job satisfaction on the performance of employees at PT. Djarum Kudus. The number of samples used in this study were 50 respodents.Data collected through the distribution of questionnaires used the sensus sampling. Measurement in the questionnaires using a Likert Scale. The method used in this study uses quantitative methods while the data analysis used is multiple linear regression analysis and also performs validity test, rebility test, classic assumption test, coefficient of determination test, F test and t test.Based on the result of multiple linear regression test, the result show that quality of work life has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Job satisfaction has positive and not significant effect on employee performance. This can be seen from the result of the R square value of 0,874, which means the employee performance can be explained by the three independent variables of 87,4%, while the remaining 12,6% is explained by other causes outside the study.